EXPERT WITNESS AND TAX FRAUD PREVENTION IN FEDERALLY COLLECTED TAXES IN NIGERIA: AN EMPIRICAL ANALYSIS - Dada, Samuel O. & Audu, Monday A. (International Journal of Research Science and Management, 2021)
The debilitating effect of tax frauds has been a major source of concern for nation states especially in developing countries such as Nigeria. This unwanted situation is further worsened by the need of the government to broaden its revenue base to combat severe economic headwinds orchestrated by the global pandemic and rapid decline in crude oil prices. Consequently, this study examined expert witness as a tool to prevent tax frauds in federally collected taxes in Nigeria. The survey research design approach was adopted for the study. Data was obtained via a structured questionnaire administered to a population made up of staff members of the Federal Inland Revenue Service (FIRS) and the four main professional accounting firms reputable for rendering forensic accounting investigation services in Nigeria. A sample size of 254 out of 394 respondents was selected using the purposive sampling technique. Reliability of data was premised on a test of internal consistency using the Cronbach Alpha Reliability approach while inferential and descriptive statistics were used to analyze the data. The study found that expert witness had a significant positive effect on tax fraud prevention (AdjR2= 0.292, F-Stat =5.180; Pvalue=0.00 < 0.05). The study recommended that the training routine of the FIRS staffs be further fortified so as to scale up their proficiency in forensic accounting while the government should consider setting up of witness protection schemes to further increase the confidence of expert witnesses and guarantee their safety.